How do warmth, safeness and connectedness-related memories and experiences explain disordered eating? - Ferreira, C. (2017)
Literature suggested that the recall of early positive experiences have a major impact on the promotion of feelings of connectedness and social safeness, and seems to protect individuals against psychopathology. Recent research has also demonstrated that the absence of these positive rearing memories play a key role on disordered eating-related behaviours. The impact of early affiliative memories on disordered eating do not seem to be direct, and the mechanisms underlying this relationship are scarcely investigated. The present study aimed to clarify how memories of warmth and safeness explain the adoption of disordered eating attitudes, and tested the mediator role of social safeness, external shame and appearance-focused social comparison on aforementioned relationship, in a sample of 277 young women. The tested model explained 36% of eating psychopathology’s variance and presented an excellent fit. Path analysis results indicated that the impact of rearing memories on eating psychopathology was fully mediated through the mechanisms of social safeness, external shame and appearance-focused social comparison. Specifically, these findings suggested that the extent to which positive rearing memories are associated with lower levels of disordered eating attitudes is influenced by the current feelings of social safeness and connectedness, which in turn are totally carried by decreased feelings of external shame and by lower endorsement on unfavourable comparison based on physical appearance with proximal targets (peers). These results seem to offer important insights for research and clinical work on body image and eating-related difficulties, suggesting the relevance of promoting warm and safe interactions with others.